Kesempurnaan Suluk Dan Adab Para Murid - Valentina Adinda Febriani (Spiritualita, 2021)
Here I will discuss about the perfection of mysticism and etiquette of the students. The first thing I will discuss is about Suluk, then in the Suluk chapter I will explain about the meaning of Suluk, the types and then the obligations of students in carrying out the exercises. Then I will explain about "what is the perfection of mysticism?" and lastly I will explain about the manners of the students. Well, the manners of these disciples include: adab to Allah, etiquette to Murshid, adab to oneself and the last adab to relatives or friends who are commonly called ikhwan